Fitness technologies in the comprehensive formation of the mobility of the musculoskeletal system and general endurance of female university students - Kraynik, V.L. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to justify and develop a set of exercises based on fitness technologies for improving the mobility of the musculoskeletal system and overall endurance of female university students and to recommend them for practical use. Methods and structure of the study. The study was conducted at Altai State Pedagogical University in 2024-2025 among first- and second-year female students. A total of 70 female students participated in the study. The following research methods were selected to gather factual material: analysis of scientific and methodological materials on the research topic, interviews, questionnaires, abstraction, generalisation, physical fitness testing, pedagogical observations, collection of practical material and its processing using mathematical statistics methods. Results and conclusions. The preliminary analytical material presented shows that important indicators of physical fitness, such as spinal mobility and overall endurance of female students, are at a low level, and it is necessary to improve the content of physical education for female students at the university based on the design of fitness technologies. The introduction of fitness aerobics exercise complexes into the physical education programme for female university students will help to increase their motivation for physical activity.